Minutes of the Twenty-ninth Regular Meeting of the Rocky Mountain Coal Mining Institute held at Denver, Colorado May 26, 27, 28, 1930 (Rocky Mountain Coal Mining Institute, 1930)
The twenty-ninth regular meeting of the Rocky Mountain Coal Mining Institute was called to order at 11:30 o'clock a. m., Monday, May 26, 1930, President B. W. Snodgrass presiding: PRESIDENT SNODGRASS (condensed report): The meeting will please come to order. As President of your Institute, I take pleasure in welcoming you to this convention, and to those who come from outside of the city, I take pleasure in Welcoming you to the city of Denver. This is the first convention at Denver in fifteen months. I hope that the annual rather than the semi-annual meetings will prove satisfactory to all, and that no mistake has been made in that respect. We are gathered together here to discuss problems common to all of us, and I am sure that we will profit by such discussion. We have with us, outside of the membership of our organization, representatives of two other organizations, Mr. Callbreath of the American Mining Congress, and Mr. Huntress of the National Coal Association. We will be honored by having them with us, and we shall expect to hear from them during this meeting.